2021
DOI: 10.1002/1878-0261.12974
|View full text |Cite
|
Sign up to set email alerts
|

Reduced WNT5A signaling in melanoma cells favors an amoeboid mode of invasion

Abstract: Tumor cells invade and spread via either a mesenchymal or an amoeboid mode of migration. Amoeboid tumor cells have a rounded morphology and pronounced RhoA activity. Here, we investigate how WNT5A signaling, a tumor promotor in melanoma, relates to Rho GTPase activity and amoeboid migration. We compared melanoma cells with low (HTB63 cells) and high (WM852 cells) WNT5A expression. HTB63 cells exhibited an amoeboid morphology and had higher RhoA activity but lower invasiveness than WM852 cells in a three-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…While RHOJ and CDC42 have not been found to be mutated in melanoma, they are often overexpressed ( Tucci et al, 2007 ). CDC42 regulates melanoma invasion and is activated in BRAF-resistant melanoma cells ( Gadea et al, 2008 ; Jobe et al, 2021 ; Lu et al, 2017 ). RHOJ regulates chemoresistance, invasion, and tumor angiogenesis in melanoma ( Ho et al, 2012 , 2013 ; Kim et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…While RHOJ and CDC42 have not been found to be mutated in melanoma, they are often overexpressed ( Tucci et al, 2007 ). CDC42 regulates melanoma invasion and is activated in BRAF-resistant melanoma cells ( Gadea et al, 2008 ; Jobe et al, 2021 ; Lu et al, 2017 ). RHOJ regulates chemoresistance, invasion, and tumor angiogenesis in melanoma ( Ho et al, 2012 , 2013 ; Kim et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylation and thereby the activation of MARCKS is traditionally considered to be due to PKC activity, although the literature suggests that MARCKS phosphorylation can also be induced via the RhoA/Rho-associated kinase (ROCK) signaling pathway [ 41 , 42 ]. This possibility is of particular interest for the present study since the WNT5A ligand has been demonstrated to activate both PKC and RhoA signaling in human melanoma cells [ 18 , 21 , 43 ]. Regarding PKC, there are nine PKC isozymes encoded by nine specific genes; however, only six have been associated with melanoma pathogenesis [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our results revealed that BRAFi-sensitive A375, A375-R1 and A375-R2 melanoma cells exhibited similar expression levels of RhoA ( Figure 7 C). However, when we measured RhoA activity [ 43 ], we found that both A375-R1 and A375-R2 cells exhibited significantly higher RhoA activity levels than their BRAFi-sensitive counterpart ( Figure 7 D).…”
Section: Resultsmentioning
confidence: 99%
“…WNT5A is a glycosylated and lipid-modified secreted protein ligand that triggers mainly the activation of noncanonical WNT signaling pathways. A recent study explored how WNT5A activity relates to the invasion mode of melanoma cells [ 212 ]. Suppressed WNT5A signaling led to a MAT that reduced the Cdc42-modulated invasion.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Suppressed WNT5A signaling led to a MAT that reduced the Cdc42-modulated invasion. Remarkably, dual targeting of WNT5A and RhoA activity revealed a more efficient approach to inhibiting melanoma cell metastasis compared to the restoration of individual targets alone [ 212 ]. Increasing evidence has indicated that the biological properties of microtubules, an element of the cytoskeleton, and their dynamics are closely correlated with invasion plasticity [ 213 ].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%